CURRENT STATUS OF PROBLEM: CHILDREN WITH RECURRENT RESPIRATORY INFECTIONS - V.A. Bulgakova; I.I. Balabolkin; V.V. Ushakova (Union of pediatricians of Russia, 2007)
The article deals with children suffered from recurrent respiraatory infections. The authors attempted to summarize the literature data on the research findings of inosine pranobex application (Isoa prinosine, Teva, Israel) in complex therapy against virulent and inflammatory diseases. Within recent years, many experts emphaasize the persistence of viruses and other pathogenic microorganaisms in the human body, which leads to changes in reactivity and emergence of the chronic diseases. These disorders are especially urgent for sickly children, suffering from respiratory infections, what well justifies the application of bacteriogenic immunomodulaa tors, interferon synthesis inductors, expediency for incorporating immunomodulators with antiviral action into complex therapy along with special vaccination against flu, pneumococcus and etc.Key words: sickly children, acute respiratory infections, immunomodulators, inosine pranobex.